IMPROVING UNDERSTANDING OF SELF-CHARACTER FOR BETTER PERSONALITY IN SD NEGERI KADILANGU 1 DEMAK - Evi, Evi (TEMATIK, 2022)
Abstract Basically, Education is an effort to improves ability human resources so that could becomes people who have character and could life independent. Based on Thing, which becomes problem in this study is, can character education create a better personality? The purpose of this study is to find out how education character could influence people to be a better person. Education character becomes important issues these days to overcome the social problems that often plague this country. It is an alternative solution that needs to be preserved in everyday life. No exception in educational institutions, which incidentally as a place for children to learn. In order to increase the understanding of the students characters of SD Negeri Kadilangu 1 Demak, a socialization was held about understanding various kinds of human characters and how to have a better character. So that later, it can be implemented to determine character and direct students to become better individuals. The holding of socialization to students regarding self-character, allows students to be able to address a problem they are facing, can distinguish between good and bad, and also be able to control the emotional self of the students of SD Negeri Kadilangu 1 Demak. Keywords: Character Education, School, Better Personal